Teaching-learning of Biology for sustainable development: The use of strategic intervention materials - Balogun, Sakirat Adenike; Olalekan, Abass Adebayo (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2024)
The research examines how Strategic Intervention Material affects the Academic Achievement of Biology Students in Senior Secondary Schools within Epe Local Government Area, Lagos state. The study uses a pre-test, post-test control group quasi-experimental design with a 2x2 factorial matrix. The sample size consists of 239 SSII students from public co-education secondary schools in the study area. Four schools were randomly selected, with two schools each assigned to the experimental and control groups. The research instruments include the Strategic Intervention Material (SIM) in biology, a lesson plan, and a 20-item multiple-choice biology achievement test (BAT), which was subjected to thorough face and content validity and had a reliability coefficient of 0.82 using the Kuder-Richardson 21 formula. Three hypotheses were formulated to guide the study and were analyzed using descriptive and inferential statistics of the t-test. The study found a significant main effect of the strategy on the academic achievement of biology students. Students who were exposed to the use of the strategic intervention material package obtained significantly higher mean scores than their counterparts in the conventional group. The study also found no significant difference between the mean achievement scores of male and female students exposed to the SIM package. It is recommended that SIM should be incorporated into teacher education programs in tertiary institutions to educate teachers in training about its importance and use, and seminars, conferences, and workshops should be organized for in-service secondary school teachers to train them in the knowledge and skills of its effective use to enhance student academic achievement in biology.